Analisis Pengelolaan Persediaan Obat Di Instalasi Farmasi Rumah Sakit Khusus Bedah Ring Road Selatan Daerah Istimewa Yogyakarta - Holo, Kristina; Siyamto, Yudi; Ary Subiyantoro (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
The aim of this research is to obtain information regarding drug management studies in terms of planning, procurement, distribution, use and disposal carried out at the Pharmacy Installation of the South Ring Road Special Surgical Hospital D.I.Y. This type of qualitative research is descriptive. Three informants participated in this research: the head of the pharmaceutical installation, the head of the pharmaceutical installation warehouse, and the person in charge of inpatient services. The results of the research show that drug management is carried out using national and hospital formularies, namely in the form of an integrated information system, which in its implementation meets the standards of the Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016, namely procurement, receipt, storage, distribution and monitoring. The obstacle experienced is the lack of stock of medicines for heart, hypertension and diabetes mellitus, for this reason regular monitoring is needed to overcome stock problems and to be able to collaborate with various parties in dealing with this so that it is efficient and effective.